2019
DOI: 10.3390/ani9060284
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Infusion of Sodium Propionate Promotes Intestinal Development and Jejunal Barrier Function in Growing Pigs

Abstract: Short-chain fatty acids (SCFAs) produced by microbial fermentation facilitate the differentiation and proliferation of intestinal epithelium. However, the role of individual SCFAs, such as propionate, on intestinal development is still unclear. In the present study, sixteen barrows fitted with a cecal fistula were randomly divided into two groups for cecal infusion of either saline (control group) or sodium propionate (propionate group). After 28 days, the length and the relative weight of intestinal segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Acetate and propionate are mainly transported to the liver through the portal vein and participate in energy metabolism ( 35 ). Recent research also revealed that propionate had positive effects on the intestinal development and barrier function of pigs ( 36 ). Therefore, the improved SCFA profile in TBZC group was able to provide additional energy available to weaned piglets and may be conducive to improving gut health.…”
Section: Discussionmentioning
confidence: 99%
“…Acetate and propionate are mainly transported to the liver through the portal vein and participate in energy metabolism ( 35 ). Recent research also revealed that propionate had positive effects on the intestinal development and barrier function of pigs ( 36 ). Therefore, the improved SCFA profile in TBZC group was able to provide additional energy available to weaned piglets and may be conducive to improving gut health.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that an increase in propionate in the hindgut could contribute to intestinal development and enhancement of jejunal barrier integrity [ 39 ]. Furthermore, the increase in butyrate concentration in the large intestine could not only enhance animal growth but also improve the intestinal mucosal environment in weaned piglets and growing pigs [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that an increase in propionate in the hindgut could contribute to intestinal development and enhancement of jejunal barrier integrity [30]. Furthermore, the increase in butyrate concentration in the large intestine could not only enhance animal growth but also improve the intestinal mucosal environment in weaned piglets and growing pigs [31][32].…”
Section: Discussionmentioning
confidence: 99%